An amphioxus gC1q protein binds human IgG and initiates the classical pathway: Implications for a C1q‐mediated complement system in the basal chordate. Issue 12 (30th October 2014) - Gao, Zhan; Li, Mengyang; Ma, Jie; Zhang, Shicui
Abstract : The origin of the classical complement pathway remains open during chordate evolution. A C1q‐like member, BjC1q, was identified in the basal chordate amphioxus. It is predominantly expressed in the hepatic caecum, hindgut, and notochord, and is significantly upregulated following challenge with bacteria or lipoteichoic acid and LPS. Recombinant BjC1q and its globular head domain specifically interact with lipoteichoic acid and LPS, but BjC1q displays little lectin activity. Moreover, rBjC1q can assemble to form the high molecular weight oligomers necessary for binding to proteases C1r/C1s and for complement activation, and binds human C1r/C1s/mannan‐binding lectin‐associated serine protease‐2 as well as amphioxus serine proteases involved in the cleavage of C4/C2, and C3 activation. Importantly, rBjC1q binds with human IgG as well as an amphioxus Ig domain containing protein, resulting in the activation of the classical complement pathway. This is the first report showing that a C1q‐like protein in invertebrates is able to initiate classical pathway, raising the possibility that amphioxus possesses a C1q‐mediated complement system. It also suggests a new scenario for the emergence of the classical complement pathway, in contrast to the proposal that the lectin pathway evolved into the classical pathway.